2021
DOI: 10.3389/fpsyg.2021.607152
|View full text |Cite
|
Sign up to set email alerts
|

How Does a Sport Psychological Intervention Help Professional Cyclists to Cope With Their Mental Health During the COVID-19 Lockdown?

Abstract: All around the world in March, due to COVID-19, competitive sport calendars were suddenly canceled, jeopardizing the training programs of athletes. Moreover, in Italy, the government banned all non-essential travel across the entire country from the beginning of March. Consequently, Italian cyclists were banned from leaving their homes and therefore unable to perform their ordinary training activities. The Italian Association of Professional Cyclists (ACCPI) early on during that period noticed that several cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 63 publications
(90 reference statements)
1
13
0
1
Order By: Relevance
“…Fostering of meaning-making processes (“normalization”) in light of the pandemic (i.e., recognition that stress reactions are normal given the current situation) represents a promising approach for psychological intervention ( Castiglioni and Gaj, 2020 ): Promoting the understanding of stressful experiences can be considered as an important coping strategy and can substantially contribute to improving sense of coherence. Complementary pandemic-compatible strategies to improve mental health are already available, such as sports psychology interventions ( Bertollo et al, 2021 ), specific pandemic-related training and preparation ( Reverté-Villarroya et al, 2021 ), and the use of interventions such as mindfulness and a reduction of news consumption ( Aughterson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fostering of meaning-making processes (“normalization”) in light of the pandemic (i.e., recognition that stress reactions are normal given the current situation) represents a promising approach for psychological intervention ( Castiglioni and Gaj, 2020 ): Promoting the understanding of stressful experiences can be considered as an important coping strategy and can substantially contribute to improving sense of coherence. Complementary pandemic-compatible strategies to improve mental health are already available, such as sports psychology interventions ( Bertollo et al, 2021 ), specific pandemic-related training and preparation ( Reverté-Villarroya et al, 2021 ), and the use of interventions such as mindfulness and a reduction of news consumption ( Aughterson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies revealed that athletes who received such professional psychological help coped better with psychological stressors, showing improved well-being than those who did not participate in such training. Online interventions give new opportunities and allow to help athletes wherever they are [35].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we see in the current study that Polish athletes, especially women, have a stronger response to the lockdown situation, which should receive particular interest. Numerous studies show that athletes all around the world experienced a decrease in mental wellbeing, an increased level of stress, anxiety, depressive symptoms and feelings of anger, confusion during the first lockdown, and women and individual sports representatives seem to have the highest costs of the problematic situation of pandemic [1,9,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Many sports associations have introduced specially prepared online psychological interventions for athletes. Furthermore, studies revealed that athletes who received such professional mental training coped better with psychological stressors, showing improved well-being than the athletes who did not participate in such training [19]. Therefore, monitoring the mental conditions of sports professionals and designing psychological interventions that would match athletes' personal needs seems crucial for similar, tremendously complex, and socially isolating situations.…”
Section: Discussionmentioning
confidence: 99%